Early emergence of motivational and hedonic feeding deficits in the TgF344-AD rat model of Alzheimer’s disease - Ostlund, Sean B.; Chen, Grace; Kosheleff, Alisa; Lueptow, Lindsay M; Zhuravka, Irina; Frautschy, Sally A.; Lam, Hoa A.; Maidment, Nigel T. (Frontiers in Aging Neuroscience, 2025)
IntroductionAlzheimer’s disease (AD) is characterized by progressive cognitive decline and has a long prodromal phase during which subclinical cognitive deficits and neuropsychiatric symptoms may begin to emerge. Apathy, defined as a lack of motivation or volition, is increasingly recognized as a core feature and a potentially early marker of AD. Despite its significance, apathy-like behavior has been underexplored in transgenic models of AD.MethodsWe performed a longitudinal analysis of apathy-like behavior using the well-established TgF344-AD rat model. We compared male and female TgF344-AD and wildtype rats on hedonic (palatable food intake) and motivational (progressive ratio) assays during early (3—4 months), intermediate (6–7 months), and later (9–10 months) stages of adulthood.ResultsWe found that female TgF344-AD rats exhibited early and persistent deficits in motivational and hedonic feeding, emerging at 3–4 months and 6–7 months, respectively. During a battery of cognitive tests conducted after 12–14 months of age, TgF344-AD rats were impaired in spatial working memory but also showed wide-ranging deficits in exploratory behavior, which may also be indicative of an apathy-like loss of investigatory drive.ConclusionOur findings highlight the TgF344-AD rat as a valuable model for studying early apathy-like behavior in AD and underscore the need to consider sex differences in AD research to better understand the prodromal phase of this disease.